The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1051/0004-6361/201936280
|View full text |Cite
|
Sign up to set email alerts
|

Could bow-shaped magnetic morphologies surround filamentary molecular clouds?

Abstract: Context. A new method based on Faraday rotation measurements recently found the line-of-sight component of magnetic fields in Orion-A and showed that their direction changes from the eastern side of this filamentary structure to its western side. Three possible magnetic field morphologies that can explain this reversal across the Orion-A region are toroidal, helical, and bow-shaped morphologies. Aims. In this paper, we constructed simple models to represent these three morphologies and compared them with the a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 46 publications
5
55
0
Order By: Relevance
“…In this scenario, the flow of matter would be initially generated by the bending of the ambient Bfield lines induced by an interstellar shock compression. Such a bent structure of the B-field lines around elongated molecular clouds is compatible with the observational findings of Tahani et al (2018) and Tahani et al (2019). Large scale CO molecular line observations have suggested that NGC 6334 may be located at the shock front of the collision of two clouds (Fukui et al 2018).…”
Section: The B-field Structure Of a High-mass Star Forming Hub-filamesupporting
confidence: 78%
“…In this scenario, the flow of matter would be initially generated by the bending of the ambient Bfield lines induced by an interstellar shock compression. Such a bent structure of the B-field lines around elongated molecular clouds is compatible with the observational findings of Tahani et al (2018) and Tahani et al (2019). Large scale CO molecular line observations have suggested that NGC 6334 may be located at the shock front of the collision of two clouds (Fukui et al 2018).…”
Section: The B-field Structure Of a High-mass Star Forming Hub-filamesupporting
confidence: 78%
“…These studies suggest that the the line-of-sight magnetic field in this region (including error bars) might have a maximum strength, 440 μG, that is smaller than 25% of the minimum plane-of-sky magnetic field strength in the OMC-1 region. The magnetic field strength along the line of sight is weaker than that in the plane of the sky, which is consistent with the bow-shaped magnetic field morphology suggested by Tahani et al (2019). Tahani et al (2018) estimated magnetic field strengths in the Orion A cloud using a new technique based on rotation measure.…”
Section: Mass-to-flux Ratiosupporting
confidence: 82%
“…The LOS velocity distributions of H I and CO lines suggest compression of the molecular cloud by an expanding ISM shell associated with the Per OB2 association (Sancisi 1974;Sun et al 2006;Shimajiri et al 2019). Furthermore, the LOS B-field morphology around the molecular cloud (Tahani et al 2018; see also Tahani et al 2019) hints at deformation of the large-scale B-field by the compressed molecular cloud.…”
Section: Discussionmentioning
confidence: 86%